Práticas inovadoras de governança na constelação local de resíduos sólidos em Cascavel - PR - Silveira, Aline Dario (2017)
The Social Practice Theory supports that the place of human coexistence is a space of being and of intelligibility and happens in meshes of practices and material arrangements that differ between them in space-time extension or in scale of its practices-arrangements sharing the horizontality of the social life. This theoretical proposal was embraced by the present thesis, whose general objective was to understand how the innovative practices of governance in the local solid waste constellation are developed in the municipality of Cascavel, state of Paraná. The adopted methodology is configured by the qualitative approach and case study, with theoretical sampling and gradual selection of the sample. The multi-actor and multi-local aspects were explored during the data collection, which used resources such as observation and interview (with the double and in depth) as main research instruments. The temporal perspective was transactional (May/November 2016). The unit of analysis was the practice and the analysis level was the local solid waste constellation. In the circular movement between data collection and analysis, the entwinement between practices emerged as well as the junction in bundles and these configuring the local constellation. The direction of this view was supported by the National Policy on Solid Waste. The thesis of this study was established in the following terms: The National Solid Waste Policy (PNRS in Portuguese), promulgated by Law 12.305/2010, as a constituent rule of municipal solid waste practice and intervention policy provides a favourable context for changes in bundles of practices and solid waste arrangements, especially in innovative actions related to governance present both in the practices themselves and in specialized governance bundles. Field research enabled the recognition of the main activities constituent of practices and practice bundles, as well as the governance initiatives that promoted changes in practices and arrangements, creation of new practices and other actions considered innovative in their contexts. The results pointed to the formation of four bundles with spatial extent limited to the local constellation of waste solid and eight bundles that extrapolate these borders. The predominant relationships in the local constellation of solid waste (i) between practice and arrangement was constitutive; (ii) between practices and between arrangements was the sharing of activity space and the chain of action; (iii) in the chain of action the predominance was governance and monitoring; and (iv) in the local constellation, the concepts prevailing in bundles dynamics were interweaving, bifurcation and stability. New concept was proposed to characterize the bundles dynamics: polyplasis, meaning that the social phenomenon is characterized by several points of formation, acting autonomously and performing peripheral actions in a decentralized governance model.